2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9176504
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Consecutive Ambient Air Pollution and Chronic Obstructive Pulmonary Disease Hospitalization: Time Series Study During 2015-2017 in Chengdu China

Abstract: This paper investigates the association between consecutive ambient air pollution and Chronic Obstructive Pulmonary Disease (COPD) hospitalization in Chengdu China. The three-year (2015-2017) time series data for both ambient air pollutant concentrations and COPD hospitalizations in Chengdu are approved for the study. The big data statistic analysis shows that Air Quality Index (AQI) exceeded the lighted air polluted level in Chengdu region are mainly attributed to particulate matters (i.e., PM 2.5 and PM 10).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several previous studies also suggested an association of PM with respiratory diseases. For example, three studies [ 8 , 17 , 18 ] reported an association between PM and COPD and two other studies reported that short-term and long-term exposure to PM 2.5 and PM 10 increased the risk of COPD [ 19 , 20 ]. Three other studies [ 21 – 23 ] examined the influence of daily PM concentrations on the number of asthma-related admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies also suggested an association of PM with respiratory diseases. For example, three studies [ 8 , 17 , 18 ] reported an association between PM and COPD and two other studies reported that short-term and long-term exposure to PM 2.5 and PM 10 increased the risk of COPD [ 19 , 20 ]. Three other studies [ 21 – 23 ] examined the influence of daily PM concentrations on the number of asthma-related admissions.…”
Section: Discussionmentioning
confidence: 99%